The primordial end calculus of prime numbers and mathematics - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
This Manuscript on the end primordial calculus of mathematics is a new discovery of the spiral nature of the entire mathematical grid at 1:3 by the precise and absolute concordance of regular number spirals and the Prime number spirals based on numbers and their spaces by grid. It is exclusive to IJAMR which has published 8 papers of the author on this new mathematics.  The manuscript has NOT been offered to any other journal in the world .The editorial board of Princeton University, USA, Annals of mathematics had been duly informed by letter of the new discovery of the concordance of prime numbers spirals with regular number spirals, but for the sake of fidelity. Mathematics is not complexity, but simplicity, the configuration of 1 is spiral .The relationship between pure mathematical numbers and empty space is a primordial relationship, and well defined by  gaps, plus it has been validated by the author by the Publishing of the pure  continuous  Den-Otter  Prime number sieve at 1/6 and 5/6 ( and 1/3 and 2/3),and these prime  sieves are reversible .Thus the relationship of the configuration of 1 is in two planes that expand in the frame of (5/6 and 1/6 ) and (1/3 and 2/3)are represented by spiral configuration , expressed  by these  numbers, as in :All prime  numbers spirals are assigned infinitely by the simple -1 offset of the  two spiral numbers cords 1/3+2/3=1 5/6+1/6=1 1/3-1/6=1/6 5/6-2/3=1/6 1/3+1/6=0.5 5/6+2/3=1.5 1.5/0.5=3 Note: the above is also confirmed by Arabian numerical shown below. Primordial mathematics as created by the creator is absolute and precise whilst the mathematics invented by man is approximate .Current Mathematics of a thousand years has accomplished much by approximate theory, and it is very possible to land a man on the moon by approximate mathematics, but to precisely understand mass and energy, the nucleus of mass and the vastness of space, one must understand the precise nature and curvature of space. Space and mathematics are curved precisely at 1:3 from primordial times( the basis for the ? as shown under the publication Unified Theorem), and the warping of space is related to the 1:3 separation at precise 19 correct degrees separation and the precise right angled separation at 1:3 is at 360/19 degrees.  This mathematics is about the curved lay of the grid of mathematics and cannot be understood by the current linear obsession of mathematics, but the readers are immediately referred to the 8 published papers of the author as referenced below. The calculus below virtually negates the current mathematics ideas of linear ascension theories of the past 500 years. This calculus is true for all prime numbers. This involves a precise “combing” of all prime number spirals around a half line. This is clearly and singularly the solution to prime number spiral calculus, which is fairly simple after this discovery. The ruminations of George Riemann and others of the past 500 years in linear ascension mathematics of prime numbers are non- functional irrelevant mathematics, just collateral observations of the correct mathematics which is presented here as “Primum movens” of mathematics. In Mathematics there is only a single best resolution, whilst collateral equations abound, as they have for 500 years for prime numbers which we have proved are basically by two chords and ascend by a half-line. Einstein’s observations and ruminations likewise are collateral and not central to the fact that the universe is precisely curved, and ascension of prime numbers are by two spiral chords.